Sejarah Ekonomi Masyarakat Muslim Bengkalis Dekade 1980-1990 - Saiful Bahri (LPPM ISNJ Bengkalis, 2020)
Government policies both in fiscal and monetary terms are the foundation of economic growth. Good governance will get good results. Above all, there is the Islamic Sharia which in turn brings the economy to its own balance. Like that happened in Bengkalis last time. The faith, piety and patience of the Muslim community make Bengkalis not only prosperous, but it is also safe and secure until today. In the 1980-1990 decade, as is commonly known, it was a transitional era in all aspects of life, and in many places, the same phenomena were found. Like the difficulty of life, inadequate infrastructure, lack of transportation and so forth, in essence, provide lessons for later generations to always be grateful to Allah for all the abundance of grace and blessings of Allah.